2011
DOI: 10.1128/mcb.05114-11
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Leads to Na,K-ATPase Downregulation via Ca2+ Release-Activated Ca2+ Channels and AMPK Activation

Abstract: 2؉concentration while a STIM1 mutant rescued the AMPK activation, suggesting that ROS act upstream of Ca 2؉ signaling. Furthermore, inhibition of CRAC channel function in rat lungs prevented the impairment of alveolar fluid reabsorption caused by hypoxia. These data suggest that during hypoxia, calcium entry via CRAC channels leads to AMPK activation, Na,K-ATPase downregulation, and alveolar epithelial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
140
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 136 publications
(151 citation statements)
references
References 60 publications
(86 reference statements)
8
140
0
3
Order By: Relevance
“…Barrier integrity likely contributes to the overall development of pulmonary edema, but the current studies by Peteranderl and colleagues clearly demonstrate that TRAIL also impairs alveolar fluid clearance independent of programmed cell death (10). This study also merges nicely with previous publications by several of these coauthors who describe hypoxia and hypercarbia as inducers of AMPK activation, a critical step for Na,K-ATPase endocytosis (14)(15)(16). These stimuli increase intracellular ROS and/or calcium and converge on PKC-ζ, which phosphorylates Na,K-ATPase to induce its endocytosis.…”
Section: Influenza Causes Pulmonary Edemasupporting
confidence: 73%
“…Barrier integrity likely contributes to the overall development of pulmonary edema, but the current studies by Peteranderl and colleagues clearly demonstrate that TRAIL also impairs alveolar fluid clearance independent of programmed cell death (10). This study also merges nicely with previous publications by several of these coauthors who describe hypoxia and hypercarbia as inducers of AMPK activation, a critical step for Na,K-ATPase endocytosis (14)(15)(16). These stimuli increase intracellular ROS and/or calcium and converge on PKC-ζ, which phosphorylates Na,K-ATPase to induce its endocytosis.…”
Section: Influenza Causes Pulmonary Edemasupporting
confidence: 73%
“…Of note, Herrero-Martín et al demonstrated that rTRAIL was able to activate AMPK in immortalized epithelial cells and, thus, promote autophagy, a cytoprotective mechanism rendering cells more resistant to deleterious challenges (57), highlighting the complexity of the IFN/TRAIL network in cellular injury and protection in response to cellular stress. The Na,K-ATPase has been well documented to be targeted for downregulation via a pathway that requires AMPK and subsequent activation of PKCζ in response to stimuli that threaten metabolic homeostasis, including alveolar hypercapnia and hypoxia (27,28). We demonstrate activation of AMPK signaling by paracrine mediators in response to IAV infection, resulting in reduced vectorial sodium transport.…”
Section: 7mentioning
confidence: 88%
“…MIF and D-DT Regulate AMPK in a Redox-dependent Fashion-Two independent studies recently described an important role for ROS in facilitating intracellular calcium increases and subsequent induction of CaMKK␤-dependent phosphorylation of AMPK (40,41). Because increased glucose uptake in transformed cells enhances pentose phosphate pathway flux-mediated generation of NADPH that, in turn, is necessary for reducing glutathione (GSH) and maintaining low ROS levels (36), we hypothesized that loss of MIF and D-DT may result in inefficient glutathione reduction as a result of defective glucose uptake (Fig.…”
Section: Camkk␤ Is Required For Maximal Mif/d-dt-dependentmentioning
confidence: 99%